166. Bring your boots: wading through GI PCR panel diagnostic stewardship applications. (15th December 2022) - Bennett, Nicholas; Boyd, Sarah E; Sattler, Jeffrey; Boos, Ginny; Johnston, Cara; Humphrey, Matt; Aragon, Laura; Aragon, Laura; Essmyer, Cynthia
Abstract: Background: Infectious diarrhea is a common cause of emergency department (ED) visits and hospital admissions. Polymerase chain reaction (PCR) testing allows for quick and expansive pathogen identification and facilitates earlier targeted treatment. We implemented a multiplex gastrointestinal (GI) PCR panel in 2014. In collaboration with the Antimicrobial and Diagnostic Advisement Program (ADAP), post-launch optimization strategies have changed test use. We evaluate the impact of diagnostic stewardship initiatives. Methods: GI PCR testing was initially unrestricted for ED or inpatients within 72 hours of admission. After fielding many questions regarding interpretation, the ADAP developed a guidance document in June 2019 regarding treatment considerations for all potential organisms detected. In January 2020, organism-specific treatment considerations were embedded in the test results real-time treatment guidance (figure 1). A pre-post quality improvement assessment of the changes was performed. In August 2021, individual GI PCR panel orders were replaced with an order set containing a decision tree to provide passive guidance evaluating acute vs chronic diarrhea, assessing recent antibiotic use (to consider C. difficile testing), no testing scenarios, and avoiding repeat testing (figure 2). Figure 1 Example of templated comments for Norovirus embedded within GI PCR panel results. Figure 2 GI PCR panel order set Results: GI PCR panel use peaked in 2019 with 3, 142 tests processed. The guidance document was less helpful, requiring an external site link. Embedding organism-specific GI PCR guidance significantly improved appropriate antibiotic prescribing (77.9 vs 89.1%, p=0.001). A precipitous drop off in GI PCR test orders occurred after the COVID-19 pandemic began (1, 774 in 2020), partly attributed to supply chain issues. When comparing intra-pandemic years (2020 vs 2021), implementation of a smart order set was associated with a 51.3% reduction in orders (1, 774 vs 864) and $131, 000 in savings despite significant patient volume increases in 2021. Low use rates have persisted into the first quarter of 2022 (n=229). Conclusion: Diagnostic stewardship changes should be proactive and contextually relevant at the time of result interpretation. Antimicrobial stewardship programs are uniquely positioned to lead optimization initiatives and drive clinical and cost-effective solutions. Disclosures: All Authors : No reported disclosures.